Genetic and clinical features of Chinese patients with mitochondrial ataxia identified by targeted next‐generation sequencing - Dong, Hai‐Lin (CNS Neurosci Ther, 2018)
AIM: To characterize the mutations in mitochondrial DNA (mtDNA) and mitochondrion‐related nuclear genes (nDNA), and clinical features in Chinese patients with mitochondrial ataxia. METHODS: Targeted next‐generation sequencing (NGS) technology was performed to screen the whole mtDNA sequence and nDNA genes in a cohort of 33 unrelated ataxia patients. RESULTS: A total of 5 pedigrees were finally genetically diagnosed as mitochondrial ataxia, with 3 pathogenic mutations (m.8344A>G, m.9176T>C, and m.9185T>C), one likely pathogenic mutation (m.3995A>G) in mtDNA, and one pathogenic mutation (c.1159_1162dupAAGT, p.Ser388Terfs) in PDHA1. The prevalence of mitochondrial ataxia in our patient cohort is 15.2%. In addition, all 4 patients with mtDNA mutations experienced symptoms of ataxia with age at onset ranging from 12 to 39 years (21 ± 12.2) and developed extrapyramidal symptoms during the disease course. One male patient with pyruvate dehydrogenase deficiency showed an acute intermittent ataxia phenotype. CONCLUSIONS: Our results implicate that mitochondrial ataxia might not be as rare in Chinese as previously assumed. This study firstly defines the mutations of mitochondrial ataxia in a Chinese population by targeted NGS, which broadens the clinical spectrum of mtDNA mutations and highlights the importance of screening mtDNA and nDNA mutations among undefined ataxia patients.